Exploring Teachers' Didactic Multilingual Competence In Arabic Language Teaching As Foreign Language - Nurbayan, Yayan; Sanusi, Anwar; Ismail, Zawawi Bin; Saleh, Nalahuddin (Ijaz Arabi Journal of Arabic Learning, 2023)
Teachers' didactic multilingual competence in Arabic teaching can also help students develop their speaking skills. They can get used to correct pronunciation and intonation through this multilingual approach, which can be applied in everyday communication. This study aimed to explore teachers' didactic multilingual competence in teaching Arabic in the classroom. The approach in this study uses a mixed method. The design used in this research is the exploratory sequential design. The number of participants in the study was 30 Arabic teachers who taught at Madrasah Aliyah in the Greater Bandung area. The results of this study indicate that out of 30 Arabic teachers, (1) the teacher always identifies students' difficulties in speaking Arabic and other foreign languages by 50%, (2) The teacher never opens and presents learning material using Arabic and other foreign languages is still in the category low as much as 50%, (3) the teacher never explains the differences and similarities of Arabic with other foreign languages in conveying material (contrastive) as much as 37%, and (4) the teacher always corrects students' grammatical and phonological errors in expressing Arabic or foreign language sentences as much as 60%. The results of this study are expected to be a reference for stakeholders in the school environment in improving the didactic multilingual competence of Arabic teachers.